Online anonymous discussion between service users and health professionals to ascertain stakeholder concerns in using e-health services in mental health. (December 2013) - Jones, Ray B; Ashurst, Emily J
Implementation of e-health in mental health services requires that we are aware of stakeholders' concerns. We ascertained the views of mental health professionals and mental health service users through the (1) development of 12 topics based on the research literature, (2) presentation to 31 participants (19 mental health professionals and 12 mental health service users) and discussion in three 1-week programmes, (3) thematic analysis of transcripts, and (4) comparison with the literature to identify areas requiring attention in e-health implementation. This method of engaging mental health service users and mental health professionals was effective. We identified areas that (1) should be the first to implement (e.g. discussion forums, email, and Skype), (2) where further education and engagement are necessary before e-health methods could be used (e.g. unsupported computerised cognitive behavioural therapy, computer–patient interviewing, and patient access to online medical records), and (3) for further research (e.g. the impact of bad online experiences).